"Sham" Litigation: When Can It Arise and How Can It Be Reduced?. (December 2017) - Lianos, Ioannis; Regibeau, Pierre
In both the U.S. and the EU, the antitrust category of "sham litigation" (in the U.S.) or "vexatious litigation" (in the EU) enables a plaintiff, or a defendant in case this action forms part of a counterclaim, to argue that the introduction of litigation may constitute, under certain conditions, an infringement of competition law. This naturally leads to the question of what is a workable standard for establishing the existence of sham litigation, and how it is possible to distinguish between the legitimate use of the regulatory/litigation process and strategic attempts to use the process in order to restrict competition. Legal and economic literature, as well as the courts, have struggled to define operational tests enabling them to determine the boundaries of the "sham"/"vexatious" litigation antitrust category. This article examines the intellectual underpinnings of this form of abusive/anticompetitive conduct and puts forward a "mechanism design approach" with the aim to reduce the occurrence of sham litigation.